2003
DOI: 10.1016/s0014-5793(03)00643-4
|View full text |Cite
|
Sign up to set email alerts
|

Dimer formation of subunit G of the yeast V‐ATPase

Abstract: The G subunit of the vacuolar ATPase (V-ATPase) is a component of the stalk connecting the V 1 and V O sectors of the enzyme and is essential for normal assembly and function. Subunit G (Vma10p) of the yeast V-ATPase was expressed in Escherichia coli as a soluble protein and was puri¢ed to homogeneity. The molecular mass of subunit G, determined by Native-polyacrylamide gel electrophoresis, gel ¢ltration analysis and small-angle X-ray scattering, was approximately 28 þ 2 kDa, indicating that this protein is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…From earlier studies, it had been suggested that homodimers of subunits E, 12 H 13 and the related G subunit of the V-ATPase 14 are key structural elements of the A-and V-ATPase peripheral stalks, but these conclusions were all based on experimental data obtained for isolated, individual subunits. For example, isolated subunit H from M. jannaschii A-ATPase was shown to exist as a dimer in solution, a structural model of which was determined by small-angle X-ray scattering.…”
Section: Discussionmentioning
confidence: 99%
“…From earlier studies, it had been suggested that homodimers of subunits E, 12 H 13 and the related G subunit of the V-ATPase 14 are key structural elements of the A-and V-ATPase peripheral stalks, but these conclusions were all based on experimental data obtained for isolated, individual subunits. For example, isolated subunit H from M. jannaschii A-ATPase was shown to exist as a dimer in solution, a structural model of which was determined by small-angle X-ray scattering.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that, unlike the other stalk components, two copies of subunit G are proposed to be present in the proton pump (18), with recombinant G protein spontaneously forming a dimer in solution (22). The presence of two copies of G within each pump may explain how the smallest pump subunit can interact with four other subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Although the site within the a subunit that is in proximity to subunit C has not been determined, the cytoplasmic localization of the N-terminal hydrophilic domain of subunit a (63) makes this region a likely candidate. By contrast, the head domain of subunit C is in close proximity to subunit G. Subunit G is a 13-kDa protein present in two copies per complex (64) that appears to form a dimer (65), analogous to the coiled-coil structure observed for the b subunit in the peripheral stalk of F 1 F 0 (66). In fact subunit G and subunit b show partial sequence homology along one helical face (67) and both are tolerant to short deletions (68,69).…”
Section: Discussionmentioning
confidence: 99%